2021
DOI: 10.1177/00031348211029843
|View full text |Cite
|
Sign up to set email alerts
|

The DEPARTS Score: A Novel Tool for Predicting Discharge Disposition in Geriatric Trauma Patients

Abstract: Background Geriatric trauma patients (GTPs) represent a high-risk population for needing post-acute care, such as skilled nursing facilities (SNFs) and long-term acute care hospitals (LTACs), due to a combination of traumatic injuries and baseline functional health. As there is currently no well-established tool for predicting these needs, we aimed to create a scoring tool that predicts disposition to SNFs/LTACs in GTPs. Methods The adult 2017 Trauma Quality Improvement Program database was divided at random i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In a study of surgical wards, Sacks et al 25 showed that older age, admission from another acute care facility, partial or full functional dependency before surgery, and a higher number of comorbidities were all associated with a greater risk-adjusted OR for transfer to PAC after various operations. The studies by Yeates 10 and Sattler 24 (in a trauma setting and after total knee arthroplasty, respectively) gave similar results. Chang 27 showed that the Activity Measure for Post-Acute Care “6-Clicks” Basic Mobility Inpatient Short Form score at admission to an acute stroke unit was the only significant predictor of transfer a post-acute inpatient rehabilitation facility.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In a study of surgical wards, Sacks et al 25 showed that older age, admission from another acute care facility, partial or full functional dependency before surgery, and a higher number of comorbidities were all associated with a greater risk-adjusted OR for transfer to PAC after various operations. The studies by Yeates 10 and Sattler 24 (in a trauma setting and after total knee arthroplasty, respectively) gave similar results. Chang 27 showed that the Activity Measure for Post-Acute Care “6-Clicks” Basic Mobility Inpatient Short Form score at admission to an acute stroke unit was the only significant predictor of transfer a post-acute inpatient rehabilitation facility.…”
Section: Discussionmentioning
confidence: 58%
“…4,5 Studies of surgical and neurology wards have shown that older age and poor functional independence are risk factors for transfer to PAC. [6][7][8][9] Specific tools [7][8][9][10] have been developed to identify patients at risk of transfer to PAC and it has been shown that the use of some of these tools is associated with a shorter length of hospital stay. 9,11 Acute geriatric units (AGUs) provide specific care for frail, dependent or multimorbid older adults with acute health problems.…”
Section: Introductionmentioning
confidence: 99%
“…This method to derive and validate a novel scoring tool has previously been performed in the literature. [8][9][10] All analyses were performed with IBM SPSS Statistics for Windows version 24 (IBM Corp). Data were collected and analyzed between July 2020 and September 2020.…”
Section: Discussionmentioning
confidence: 99%
“…PREPS was then validated in the validation cohort using the AUROC curve. This method to derive and validate a novel scoring tool has previously been performed in the literature . All analyses were performed with IBM SPSS Statistics for Windows version 24 (IBM Corp).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation